2010
DOI: 10.1007/s12015-010-9126-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Bone Marrow-derived Mesenchymal Stem Cells into Hepatocyte-like Cells on Nanofibers and Their Transplantation into a Carbon Tetrachloride-Induced Liver Fibrosis Model

Abstract: There are limited data available on the effect of a physicochemical microenvironment on mesenchymal stem cell (MSC) differentiation and repopulation of the liver. Therefore, in this study nanofibers have been used to better differentiate and maintain the function and engraftment of differentiating MSCs both in vitro and in vivo. Mouse MSCs were differentiated into early (day 18) and late (day 36) hepatocyte-like cells (HLCs) in the presence or absence of ultraweb nanofibers (nano(+) and nano(-)) and their tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 45 publications
1
99
0
1
Order By: Relevance
“…We have created our nano ECM from an electrospun nonwoven matrix of polyamide nanofibers with an average fiber diameter of 280 nm [33], which was employed as a model to mimic the geometry and nanotopography of the ECM/basement membrane for cell growth [10]. The beneficial influence of this nanofibrillar surface has been reported in cultures of different somatic cells [1,2,25,27] and the differentiation of human embryonic stem cells into a hepatic lineage as well as mouse mesenchymal stem cells [13,31]. Recently, we demonstrated enhanced migration, proliferation, and morphology of neural progenitors plated on this nano-structure in comparison with their maintenance on tissue-culture plates [32].…”
Section: Discussionmentioning
confidence: 99%
“…We have created our nano ECM from an electrospun nonwoven matrix of polyamide nanofibers with an average fiber diameter of 280 nm [33], which was employed as a model to mimic the geometry and nanotopography of the ECM/basement membrane for cell growth [10]. The beneficial influence of this nanofibrillar surface has been reported in cultures of different somatic cells [1,2,25,27] and the differentiation of human embryonic stem cells into a hepatic lineage as well as mouse mesenchymal stem cells [13,31]. Recently, we demonstrated enhanced migration, proliferation, and morphology of neural progenitors plated on this nano-structure in comparison with their maintenance on tissue-culture plates [32].…”
Section: Discussionmentioning
confidence: 99%
“…There are many problems associated with this paradigm, particularly during the in vitro manipulation process and the delivery and local engraftment of re-transplantation cells [16]. Moreover, stem cell fate is influenced by a number of factors including extracellular matrices (ECMs) and interactions that require robust control for safe and effective regeneration of functional tissue [19]. Appearance of a novel field of science and technology called tissue engineering raises hope for the solution of the problems mentioned above [17].…”
Section: Introductionmentioning
confidence: 99%
“…BMMSCs induced under specific conditions can differentiate into various tissues and cells in different micro-environments. A number of studies have demonstrated that, when cultured with epidermal growth factor (EGF), hepatocyte growth factor (HGF) and basic fibroblast growth factor (bFGF) (Chivu et al 2009;Forte et al 2006;Snykers et al 2011), liver cells (Gu et al 2009;Lange et al 2005) and liver injury serum Lysy et al 2008) can induce BMMSCs to differentiate into hepatocytes in vitro and in vivo (Piryaei et al 2011;Stock et al 2010). Since growth factor protein is expensive and has a short halflife in vivo and large doses may result in hemodynamic abnormalities and serious side effects, genetherapy has become a targeted approach for delivery (Supp and Boyce 2002).…”
Section: Introductionmentioning
confidence: 99%